The Connotative Meaning of Expression Found in Adele’s Song Lyrics 21 “Japanese Edition” Album - Harsetiani, Kadek Mei (Udayana Journal of Social Sciences and Humanities; Vol 6 No 1 (2022): UJoSSH, February 2022DO - 10.24843/UJoSSH.2022.v06.i01.p04, 2022)
This study is entitled "The Connotative Meaning of Expression Found in Adele's  Song Lyrics 21 "Japanese Edition" Album". It focuses on describing the types of connotative meaning and connotative expression found in the song lyrics. This study mainly uses the theory proposed by Leech and Cruse. Methods applied in this study were qualitative methods and descriptive analysis. The data here was taken from the internet through the Genius website. The data was collected by downloading the song lyrics and then printing them out. Then, closed reading was implied to identify the expression containing connotation. Furthermore, the data were analyzed based on a semantic theory proposed by Leech (1981) and Cruse (1997). Four songs were analyzed based on the theory proposed by selecting the expression which contains connotative meaning. The result of this study shows that the expression found in Adele's song lyrics contains three types of connotative meaning, such as Positive, Negative, and Neutral. However, the negative connotations are mostly used in the expression.   The use of the expression in Adele's song lyrics is to express her feelings towards someone in her past relationship.